PENGADAAN BAHAN PUSTAKA SEBAGAI UPAYA DALAM MEMENUHI KEBUTUHAN PEMUSTAKA - Fatimah Fatimah (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2019)
Abstract : Collection Procurement is an effort made by the library to add to the collection, both printed and non-printed to meet the data needs and information of the visitors (Mathar, 2012: 105). In the procurement of a library collection materials there are functions and objectives of each. The purpose of library material procurement is to develop a good and balanced collection of library materials so as to be able to serve the changing needs of users and the demands of current and future users. (Yulia, 2009: 121). Procurement will be able to function if the source of information in the library is available library materials according to user needs. With complete library materials we can search for information and references needed.Keyword : Library Material Procurement.Abstrak : Pengadaan Koleksi adalah upaya yang dilakukan oleh perpustakaan untuk menambah koleksi, baik tercetak maupun yang tidak tercetak untuk memenuhi kebutuhan data dan inforamasi para pemustaka (Mathar, 2012:105). Dalam pengadaan suatu bahan koleksi pustaka terdapat fungsi dan tujuan masing-masing. Tujuan dari pengadaan bahan pustaka adalah Untuk Mengembangkan koleksi bahan Perpustakaan yang baik dan seimbang sehingga mampu melayani kebutuhan pemakai yang berubah dan tuntutan pemakai masa kini dan masa mendatang. (Yulia, 2009 : 121). Pengadaan akan dapat berfungsi apabila sumber informasi dalam perpustakaan tersedia bahan pustaka sesuai kebutuhan penguna. Dengan bahan pustaka yang lengkap kita dapat mencari informasi dan referensi yang dibutuhkan.Kata Kunci : Pengadaan Bahan Pustaka